Effect of Jetty Pillar Orientation on Scleractinian Corals - C.M, Lau; Y. A., Affendi; V. C., Chong (Malaysian Journal of Science, 2009)
This study investigated the effect of orientation of the Pulau Tioman Marine Park jetty pillars on the underwater light intensity, zooxanthellae density and chlorophyll content of Acropora selago (branching coral) and Cyphastrea japonica (encrusting coral). There was significant difference in Photosynthetically Active Radiation (PAR) level between orientations of jetty pillars. However, the coral cover showed no significant difference between orientations suggesting that corals are able to grow if minimum PAR level is available. In Cyphastrea japonica, the difference in zooxanthellae density was significant between pillar orientations but Acropora selago showed otherwise. This difference in C. japonica was due to their zooxanthellar adaptation to different PAR levels. The chlorophyll a and c2 content of both coral species between pillar orientations showed no significant difference. Zooxanthellae density and chlorophyll content of A. selago were almost similar compared between the jetty and the natural reef at Kampung Air Batang suggesting that the jetty’s corals are viable species. Thus, we suggest that the construction of jetties in corals reef areas should consider pillar design and orientation in order to provide hard substrate and help to rehabilitate corals in the damaged construction area.